Strategy to Identify Areas of Use of Amazon River dolphins - Mosquera-Guerra, Federico; Trujillo, Fernando; Pérez-Torres, Jairo; Mantilla-Meluk, Hugo; Franco-León, Nicole; Paschoalini, Mariana; Valderrama, María J.; Usma Oviedo, José S.; Campbell, Elizabeth; Alfaro-Shigueto, Joanna; Mena, José L.; Mangel, Jeffrey C.; et al. (Frontiers in Marine Science, 2022)
Unsustainable fisheries practices carried out in large parts of the Amazon, Tocantins, and Orinoco basins have contributed to the decline in the populations of the Amazon River dolphins (Inia spp.), considered Endangered by the International Union for Conservation of Nature (IUCN). Amazon River dolphin byproducts are often obtained through unregulated fisheries and from stranded and incidentally caught individuals that are traded for the flesh and blubber used for Calophysus macropterus fisheries, traditional and other medicinal purposes, and more recently for human consumption. To identify localities of use of Amazon River dolphins, we conducted a systematic review of the related literature published since 1980, complemented with structured surveys of researchers that allowed the identification of 57 localities for uses of Inia (33 in the Amazon, two in the Tocantins, and 22 in the Orinoco basins), and two more on the Brazilian Atlantic coast, with recent reports of targeted consumption in the upper Orinoco River. Subsequently, the localities of use or bushmeat markets where Amazon River dolphin byproducts are trafficked were identified. This information was integrated with a kernel density analysis of the distribution of the Inia spp. populations establishing core areas. Our spatial analysis indicated that the use of Inia spp. is geographically widespread in the evaluated basins. It is urgent that decision-makers direct policies towards mitigating the socioeconomic and cultural circumstances associated with illegal practices affecting Amazon River dolphin populations in South America.